Avoiding and Correcting Complications in Facial Plastic Surgery: Patient Selection - Chatham, Donn R. (Facial Plastic Surgery, 2012)
Far from being simply a cursory step, the initial consultation between the patient and plastic surgeon, when patient selection usually occurs, can be complicated. Proper patient selection is the key first step toward a successful outcome from a proposed procedure. Not only must the physical and health status of the patient be understood, but the surgeon quickly must determine whether the emotional and psychological attributes and expectations of a particular patient are up to the rigors of the particular surgery being discussed. The concepts of expectations and satisfaction, personality types, and the difficult patient will be discussed. Yes, predicting the future is part of the surgeon's valued armamentaria. But even experienced and astute physicians cannot always make perfect decisions.
Keywords: patient selection; consultation; management; difficult patient